2022
DOI: 10.22207/jpam.16.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Foot Ulcer Infections and Pseudomonas aeruginosa Biofilm Production During the COVID-19 Pandemic

Abstract: During the different waves of the coronavirus (COVID-19) pandemic, there has been an increased incidence of diabetes mellitus and diabetic foot infections. Among gram-negative bacteria, Pseudomonas aeruginosa is the predominant causative agent for diabetic foot ulcer infections in low-resource countries. P. aeruginosa possesses a variety of virulence factors, including biofilm formation. Biofilm formation is an important benchmark characteristic in the pathophysiology of diabetic foot ulceration. The main obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
3
4
0
Order By: Relevance
“…However, isolate S.au 10 was susceptible to gentamicin, ciprofloxacin, and vancomycin with inhibition diameters of 20, 28, and 24 mm, respectively. This result is similar to [34], who reported that 96 % of S. aureus strains were resistant to tetracycline and methicillin, with varying degrees of resistance to other antibiotics. Regarding P. aeruginosa, P.ae1 and P.ae4 were sensitive to all antibiotics tested, while P.ae2 was resistant to 3 antibiotics, namely amoxicillin, gentamicin, and erythromycin, with inhibition diameters of 06, 10, and 08 mm, respectively.…”
Section: Isolated Bacteriasupporting
confidence: 90%
See 1 more Smart Citation
“…However, isolate S.au 10 was susceptible to gentamicin, ciprofloxacin, and vancomycin with inhibition diameters of 20, 28, and 24 mm, respectively. This result is similar to [34], who reported that 96 % of S. aureus strains were resistant to tetracycline and methicillin, with varying degrees of resistance to other antibiotics. Regarding P. aeruginosa, P.ae1 and P.ae4 were sensitive to all antibiotics tested, while P.ae2 was resistant to 3 antibiotics, namely amoxicillin, gentamicin, and erythromycin, with inhibition diameters of 06, 10, and 08 mm, respectively.…”
Section: Isolated Bacteriasupporting
confidence: 90%
“…Among the remaining 42.86 % of gram-negative bacteria, P. aeruginosa was the most frequently detected (24 %). These findings are supported by [33,34], who also identified P. aeruginosa as the primary gram-negative bacterium responsible for diabetic wound infections. The high prevalence of S. aureus and P. aeruginosa in diabetic wounds can be attributed to their ability to utilize sugar as an energy source and also their resistance to various antibiotic classes.…”
Section: Microbiological Characteristics Of Diabetic Woundsmentioning
confidence: 56%
“…The results showed that the presence of algD gene was in a rate of 65% of the total isolates, fig (3).This is compatible with Garallah, et al (29) who got a percentage of 65.38%, but not compatible with Yang, et al (30), as the presence of this gene was 98.49% in the mentioned study. The results also showed the presence of pslD gene in a percentage of 70% , fig ( 4), this is agreed with Ghadaksaz, et al (31), as the percentage of this gene of that study was 83.7%, but didn't agree with Abdelwahab and Yakout (32) whose detected this gene in just 49.7% of their total isolates. Finally, the results showed the presence of pelF gene in 70% of the total isolates, fig (5), this is close related to the percentage of Pournajaf, et al (33), whose detected this gene in about 57.3% , but far from the results of Yanget al (30), as the gene is found in most of the bacterial isolates of that study 96.48%.…”
Section: Resultssupporting
confidence: 50%
“…The most common and severe NFGNB is P. aeruginosa , which is frequently found to be involved in a wide variety of nosocomial infections, particularly infecting patients with predisposing factors, such as burn victims, immunocompromised hosts, or those with metabolic disorders [ 15 , 16 , 17 ]. It is also recognized as a predominant cause of pulmonary disease and mortality in patients with cystic fibrosis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%